Huangkui capsule combined with finerenone attenuates diabetic nephropathy by regulating the JAK2/STAT3 signaling pathway based on network pharmacology, molecular docking, and experimental verification - Liu, Xuanke; Zhang, Chunjiang; Fu, YanJie; Dai, JingJing; Lu, Jiaying; Liu, Gang; Yang, Xiaoping (Frontiers in Pharmacology, 2025)
IntroductionDiabetic nephropathy (DN) is a serious complication of diabetes with limited therapeutic options. Although Huangkui capsule (HKC) and finerenone individually show potential in DN management, their combined mechanism remains unclear. This study aimed to explore the therapeutic effects and underlying mechanisms of HKC and finerenone combination for DN.MethodsAn integrative approach combining network pharmacology, molecular docking, kinetic simulations, and experimental validation was employed in this study. Active components of HKC and finerenone, along with their potential targets, were identified through database mining. A “drug-component-target-disease” network was constructed, and interactions with the JAK2/STAT3 pathway were validated. In vivo, DN mice were treated with HKC, finerenone, and their combination (CDI group), while in vitro, HK-2 cells were treated with quercetin (a core HKC component) and finerenone. The binding index between quercetin and finerenone was analyzed by using the Chou–Talalay method.ResultsNetwork pharmacology identified three core HKC components (quercetin, myricetin, and gossypetin) and 11 key targets (e.g., JAK2, STAT3, and AKT1). Molecular docking revealed strong binding affinity between quercetin–finerenone and JAK2/STAT3 (ΔG = −65.465 kcal/mol for STAT3-quercetin). In DN mice, combined therapy significantly reduced 24-h urinary protein (358.54 ± 21.21 mg/L vs. 1046.48 ± 72.84 mg/L in the model group, p < 0.001), improved serum creatinine/urea nitrogen, and downregulated IL-6/TNF-α expression. It also suppressed pro-apoptotic gene (Bax, Caspase-3/8, and PARP) activity while upregulating that of Bcl-2. Histopathology showed reduced tubular injury markers (NGAL and KIM-1) and fibrosis (p < 0.05). In HK-2 cells, quercetin + finerenone synergistically inhibited apoptosis and inflammation (p < 0.05), and the combined index (cl) was calculated to be less than 1. STAT3 overexpression exacerbated inflammation/apoptosis, which was reversed by combined treatment (p < 0.01).ConclusionHKC combined with finerenone mitigates DN progression by inhibiting the JAK2/STAT3 pathway and reducing inflammation, apoptosis, and tubular injury. These findings provide a mechanistic basis for clinical application of this combination therapy.